Modernes Bildgebungsverfahren in der Diagnostik der Großgefäßvaskulitiden - Haneder, Stefan; Schönberg, Stefan; Michaely, Henrik J. M.; Dinter, Dietmar (Gefässchirurgie, 2012)
This review article addresses the diagnostics of large vessel vasculitis (LVV), Takayasu vasculitis and giant cell vasculitis, with the focus on nuclear medicine techniques, namely positron emission tomography (PET) scans with 18F-fluorodeoxyglucose (18F-FDG-PET) and in combination with computed tomography (18F-FDG-PET/CT). Clinical diagnostics and duplex ultrasound still play a central role in the diagnostic workup of LVV, notwithstanding the technical improvements of these nuclear medicine techniques over the last years. The 18F-FDG-PET and 18F-FDG-PET/CT methods offer important clinical value for specific questions, such as disease dissemination or the pattern of dissemination of LVV. This article summarizes the current value and field of potential applications of 18F-FDG-PET/CT.
Gesehen am 29.11.2018